Armageddon's children [large type] - Brooks, Terry (Brooks, Terry. Genesis of Shannara., 2006)
Not so very far in the future, civilization teeters on the verge of collapse. Evil forces roam the ruined landscape of the former United States, recruiting the weak and enslaving the rest. Only pockets of resistance remain, with only a few heroes to protect them. Once such hero is Logan Tom. His mission: to locate a group of Seattle street kids and guard them with his life. Because one of them carries a magic that might - just might - be powerful enough to save the world.